A classic and fatal case of Streptococcus mutans subacute bacterial endocarditis; A now potentially underappreciated disease. (2020) - Schmalzle, SA
Abstract: Acute bacterial endocarditis is now common and easily suspected and recognized in the setting of prosthetic valves, injection drug use, or bacteremia with virulent organisms. Conversely, subacute bacterial endocarditis has drastically decreased in incidence, and recognition may be further hampered by the indolent non-specific presentation. Delayed diagnosis is common and can lead to serious complications and fatalities. We describe a patient found to have Streptococcus mutans subacute bacterial endocarditis, who presented with classic risk factors and findings, and who died shortly after presentation due to hemorrhagic conversion of an embolic stroke in the setting of anticoagulation. It is critical that all cases of streptococcal bacteremia be appropriately evaluated and treated, and that Streptococcus spp. not ever be routinely considered a blood culture 'contaminant'.